2003
DOI: 10.1023/b:joci.0000010425.30967.0f
|View full text |Cite
|
Sign up to set email alerts
|

Deficient IFN-  Expression in Umbilical Cord Blood (UCB) T Cells Can Be Rescued by IFN- -Mediated Increase in NFATc2 Expression

Abstract: Regulation of nuclear factor of activated T cells-c2 (NFATc2) gene expression is not clearly defined. We previously reported reduced NFATc2 protein expression in cord blood T lymphocytes. Here we show that NFATc2 expression in T cells is dependent in part on the presence of IFN-gamma during primary stimulation, as blocking of IFN-gamma blunted NFATc2 protein and mRNA upregulation. Conversely, addition of exogenous IFN-gamma during stimulation resulted in increased expression of NFATc2 in cord blood T lymphocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 45 publications
0
4
1
Order By: Relevance
“…In addition to the signaling pattern, we have found that Cbl-b is induced in CB naive CD4 + T cells, providing more molecular evidence that these cells may become anergic upon stimulation. Importantly, our results do not exclude other factors in contributing to impaired IFN-γ gene expression, such increased DNA methylation of the IFN-γ gene (61), reduced levels of NFATc2 in unfractionated CB CD4 + T cells (62), and altered antigen-presenting cell function (63, 64). …”
Section: Discussioncontrasting
confidence: 58%
“…In addition to the signaling pattern, we have found that Cbl-b is induced in CB naive CD4 + T cells, providing more molecular evidence that these cells may become anergic upon stimulation. Importantly, our results do not exclude other factors in contributing to impaired IFN-γ gene expression, such increased DNA methylation of the IFN-γ gene (61), reduced levels of NFATc2 in unfractionated CB CD4 + T cells (62), and altered antigen-presenting cell function (63, 64). …”
Section: Discussioncontrasting
confidence: 58%
“…During primary stimulation, naive UCB CD4 þ T cells have reproducibly exhibited both reduced Th1-associated cytokine, specifically IFN-g and TNF-a, 43,44 as well as significant changes in the composition of the transcription factors NFAT1, AP1 and BACH2. 3 Therefore, UCB CD4 þ T cell has the unique response for the co-stimulation of normal IL-2 expression coupled with rapid proliferation, which could have significant physiological and clinical ramifications in the allogeneic setting.…”
Section: Bach2's Function In Ucb Cd4mentioning
confidence: 99%
“…Presently, enrichment for Hoechst-dim cells by flow sorting is not maintained after passage. Previous work has indicated that Hoechst-dim staining is a result of the presence of the ABCG2 receptor [37,38]. As shown in Figure 1E and 1F, human UCMS (hUCMS) cells showed the characteristic surface staining for the ABCG2 receptor and CD44.…”
Section: Flow Cytometry and Sorting Of Hoechst-dim Cellsmentioning
confidence: 83%